The Influence of Social Media Attractiveness and Brand Value on the Level of Purchasing Confidence in Indonesia: Pengaruh Daya Tarik Sosial Media dan Brand Value Terhadap Tingkat Kepercayaan Pembelian di Indonesia - Rahma, Ghina Aulia; Evrynasari, Apriliana; Putri, Melia; Nasution, Siska Angreyani; Rosyidani, Nabila Masithoh (Prosiding University Research Colloquium, 2024)
This study aims to analyze the influence of social media attractiveness and brand value on the level of people's purchase trust. From the study, 100 samples were obtained from the general public who use social media to buy a product. The method in this study is a quantitative method with the results showing that the variables of attractiveness, brand value, trust, and parasocial relationships have a significant effect on people's purchase intentions. The limitation in this study is the presence of indicators that do not have a significant effect on the level of public purchasing trust through social media.